Uniportal Video-Assisted Thoracoscopic Resection and Lobectomy for Infants With Pulmonary Sequestration: Case Series and Initial Experience - Huang, Jin-Xi; Chen, Qiang; Hong, Song-Ming; Hong, Jun-Jie; Cao, Hua (Frontiers in Pediatrics, 2021)
Background: The present study aimed to evaluate the safety and feasibility of uniportal video-assisted thoracoscopic surgery (U-VATS) for infants with pulmonary sequestration (PS). Methods: From January 2019 to July 2020, 19 infants with PS were admitted to a provincial hospital in the Fujian Province of China. A 1.5-cm utility port was created in the fifth intercostal space at the anterior axillary line. A rigid 30° 5-mm optic thoracoscope was used for vision, and two or three instruments were utilized through the port. Surgical options include standard lobectomy, wedge resection, and resection of the extralobar sequestration. Only one intercostal space was entered, and a chest tube was inserted through the same skin incision if necessary. Results: The procedure was successful in all patients with an average operation duration of 58.3 ± 31.5 min. The length of postoperative hospital stay was 5.4 ± 1.5 days, and no postoperative deaths or serious complications were observed. The mean postoperative drainage volume was 164.6 ± 45.9 mL, and the mean postoperative thoracic tube indwelling duration was 5.5 ± 1.0 days. No intraoperative conversion, surgical mortality, or major complications were identified among the patients. Conclusion: Our preliminary experience presented a series of U-VATS lobectomy, wedge resection, and resection of the PS for infants with satisfactory perioperative results.